Kazakhstan - The New Pensions in Kazakhstan : Challenges in Making the Transition - World Bank (Washington, DC, 2013)
This report discuses Kazakhstan's pension system reform which is nearing the completion of the sixth year of its implementation. In addition to the need to address the design and operation of the payout phase of the pension system, the report finds two main areas in which changes and refinements to the pension system should be considered: (1) Changes to the basic benefit and financing structure of the system, during both the transitional and fully implemented stage. These should be aimed at improving the capacity of the system to provide adequate and equitable benefits; and (2) Improvements to the institutional and regulatory infrastructure to enhance the security and efficiency of the pension system. The report also provides recommendations for changes to the initial framework that would enhance the capacity of the reform to achieve the long-term goal of a sustainable, affordable and equitable pension system. This study reviews the experience gained, in the light of current conditions and projected outcomes, and draws conclusions about the likely medium and long-term consequences of the current design of the pension system. The report also provides recommendations for changes to the initial framework that would enhance the capacity of the reform to achieve the long-term goal of a sustainable, affordable and equitable pension system.